(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the author emphasizes the issues of creating a character in a work of art. In particular, the character’s way of speaking, speech, behavior, clothes, mutual description, self-description, etc., are analyzed in depth, and examples from the creative works of Stefan Zweig and Ulugbek Hamdam are given. One of the important indicators that reveal the inner world of the hero, his way of life, is the character’s speech. What the hero says and how he says it is also important. Through the speech, we learn about the hero’s nationality, social background, temperament, intelligence, abilities, level of education, about his unique characteristics.